The Situation Room as a management tool: the case of the Municipal Health Secretariat of Salvador. (30th September 2020) - Pereira, M; Santos, dos; Alves, H; Lima, Vieira; Carvalho Cerqueira, S; Almeida, A; Jure, F; Rosemberg, R; de Fernandes, Oliveira
Abstract: Problem: The Salvador Municipal Health Secretariat (MHS) utilizes health data to elaborate technical documents to manage and respond to instances requiring internal or external control. In answer to demands for the modernization and transparency of municipal management, the constitution of a Health Situation Room (HSR) was included in the political agenda of the Secretary, thereby guaranteeing political, technical and operational support for its implementation. Description of the Problem: To describe the process of construction of the HSR in the Salvador MHS in 2020. The HSR is a physical, virtual and collective space for the analysis of information, which begins with a data search which allows to understand the information flow, identifying the solicitor and the constructor of the information, the data source and the informational object itself. Results: 130 technicians and managers were interviewed, and their responses then categorized into 161 indicators across different themes. The results point out the need to define a spatial analysis unit to be adopted, and to communicate with external actors who demand information, as well as to develop a communication plan for the HSR. Lessons: To develop an informational culture oriented by local and central protagonism, generating evidence for decision-making and information transparency for the whole of society. Key messages: The Health Situation Room reduces the time between information-decision-action. The Health Situation Room prioritizes interdisciplinary collaboration and increases the efficiency of the health system.